PENEGAKAN HUKUM TERHADAP PENYALAHGUNAAN DATA PRIBADI DI INDONESIA - Anisa Hijrani; Zulfikar Jayakusuma; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
As a form of innovation, information technology is now capable of collecting,storing, sharing and analyzing data. These activities have resulted in various sectors of lifeutilizing information technology systems. Data privacy issues are something that arises whenpersonal data is given to people who are not responsible for committing crimes of misuse ofpersonal data. Privacy is a fundamental human right. Privacy is difficult to define in auniversal sense. Although privacy is difficult to define, the term privacy is used in a broadsense related to the protection of personal data. Thus, it is necessary to increase efforts andefforts to overcome these problems by the police, especially the Riau Regional Police.The purpose of writing this thesis, namely: First, Knowing the law enforcement on the misuseof personal data in Indonesia, Second What are the obstacles in regulating legal protectionagainst misuse of personal data, especially in the formulation of criminal sanctions. This typeof research is sociological legal research, namely research that wants to see the correlationbetween law and society, using interviews at the Riau Regional Police and also literaturestudies.Keywords : Law Enforcement - Misuse – Personal Data